Brånemark Novum® immediate loading rehabilitation of edentulous mandibles: 11‐year retrospective study. Issue 1 (8th November 2013) - Tealdo, Tiziano; Menini, Maria; Bevilacqua, Marco; Pera, Francesco; Capalbo, Vanessa; Pera, Paolo
Abstract Objectives Short‐term results indicated that the Brånemark Novum® protocol (Nobel Biocare AB, Goteborg, Sweden) allowed successful rehabilitation of mandibular edentulism with immediately loaded implants. Yet, long‐term studies are lacking. The aim of the present retrospective study was to report the 11‐year outcomes for patients treated according to this protocol. Material and methods Four patients treated according to the Brånemark Novum protocol (Nobel Biocare AB) were followed‐up to evaluate implant and prosthesis cumulative survival rate (CSR), implant stability (RFA), marginal bone loss by periapical radiographs, probing depth (PD), and possible complications. Clinical and radiographic parameters were evaluated immediately after completion of the treatment and 1, 5, and 11 years after loading. Results The 11‐year implant and prosthesis CSRs were 100%. Implant stability (RFA values) remained stable over the 11‐year follow‐up. Small bone resorption was found next to distal implants (median 1 mm) after 11 years, while central implants showed greater bone resorption (median 4.5 mm). The PD (mean 3.75 mm at 11 years) grew together with marginal bone loss. One implant complication was detected on a central implant (crater‐form bone destruction), and 10 prosthetic complications (fractures of resin or teeth), 80% of which registered on the same parafunctional patient. Conclusions The 11‐year results demonstrated that the Brånemark Novum protocol (Nobel Biocare AB) is a predictable technique with favorable long‐term outcomes. This was a rigid protocol, which could be applied only in patients with specific anatomical characteristics of the lower jaw, but it had the merit of indicating the key factors for full‐arch immediate loading rehabilitations.